Opportunities and challenges : the Caribbean involvement in the Free Trade Area of the Americas - Bishop, Myrtle D. (2004)
Examines the region's participation in the process leading to the establishment of the FTAA, and the benefits and challenges associated with its involvement in this hemispheric undertaking.